Pathogenic and targetable genetic alterations in 70 urachal adenocarcinomas. Issue 7 (10th May 2018) - Reis, Henning; van der Vos, Kristan E.; Niedworok, Christian; Herold, Thomas; Módos, Orsolya; Szendrői, Attila; Hager, Thomas; Ingenwerth, Marc; Vis, Daniël J.; Behrendt, Mark A.; de Jong, Jeroen; van der Heijden, Michiel S.; et al.
Abstract : Urachal cancer (UrC) is a rare but aggressive malignancy often diagnosed in advanced stages requiring systemic treatment. Although cytotoxic chemotherapy is of limited effectiveness, prospective clinical studies can hardly be conducted. Targeted therapeutic treatment approaches and potentially immunotherapy based on a biological rationale may provide an alternative strategy. We therefore subjected 70 urachal adenocarcinomas to targeted next‐generation sequencing, conducted in situ and immunohistochemical analyses (including PD‐L1 and DNA mismatch repair proteins [MMR]) and evaluated the microsatellite instability (MSI) status. The analytical findings were correlated with clinicopathological and outcome data and Kaplan‐Meier and univariable/multivariable Cox regression analyses were performed. The patients had a mean age of 50 years, 66% were male and a 5‐year overall survival (OS) of 58% and recurrence‐free survival (RFS) of 45% was detected. Sequence variations were observed in TP53 (66%), KRAS (21%), BRAF (4%), PIK3CA (4%), FGFR1 (1%), MET (1%), NRAS (1%), and PDGFRA (1%). Gene amplifications were found in EGFR (5%), ERBB2 (2%), and MET (2%). We detected no evidence of MMR‐deficiency (MMR‐d)/MSI‐high (MSI‐h), whereas 10 of 63 cases (16%) expressed PD‐L1. Therefore, anti‐PD‐1/PD‐L1 immunotherapy approaches might be tested in UrC. Importantly, we found aberrations in intracellular signal transduction pathways (RAS/RAF/PI3K) in 31% of UrCs with potential implications for anti‐EGFR therapy. Less frequent potentially actionable genetic alterations were additionally detected in ERBB2 (HER2), MET, FGFR1, and PDGFRA . The molecular profile strengthens the notion that UrC is a distinct entity on the genomic level with closer resemblance to colorectal than to bladder cancer. Abstract : What's new? Urachal cancer (UrC) is a rare but aggressive cancer. In this study, the authors analyzed a number of genes and proteins that might be altered in UrC. They found no evidence of unusual mismatch repair (MMR) or microsatellite instability (MSI) status. However, they did observe aberrations in PD‐L1‐status, and in intracellular signal‐transduction pathways (RAS/RAF/PI3K), as well as alterations in ERBB2 (HER2), MET, FGFR1, and PDGFRA. These results might provide a basis for targeted and/or immunotherapeutic approaches.